Case Study on the Knock-in Storm of Snowball Products - Yin, Zijian (Journal of Global Economy, Business and Finance, 2026)
This case study examines the 2024 “knock-in storm” of snowball products in China’s capital market. Structured as autocallable barrier options with 10%–20% annualized coupons, these products exposed investors to severe risks when the CSI 500 and CSI 1000 indices collapsed in January 2024, triggering knock-in clauses (70%–80% of initial levels) and shifting returns to index-linked losses. Causes included weak macroeconomic conditions, concentrated product maturities, clustered knock-in levels, and an asymmetric payoff structure that amplified losses. GARCH(1, 1)-t model analysis revealed underestimated tail risks in index returns. Impacts spanned investor losses, institutional hedging pressures, and market volatility. Recommendations focus on enhancing risk education, improving institutional risk management, and strengthening regulatory oversight to balance innovation and stability in derivatives markets.